Analisis Kelayakan Homestay Dalam Penerapan Prinsip Wisata Halal Di Desa Wisata Pulau Lombok - Muttaqillah, Muttaqillah; Permadi, Lalu Adi; Retnowati, Weni (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
The purpose of this study is to determine the feasibility of homestays in Lombok Island Tourism Village in the application of halal tourism principles. The method of proving the purpose of the study uses descriptive methods with a mixed method consisting of qualitative and quantitative methods. The object of study is the feasibility of homestays in the application of halal tourism principles (case study in Lombok Island Tourism Village). Primary data collection will be conducted with in-depth interviews. The results of the study that Homestays in tourist villages on Lombok Island have mostly tried to apply the principles of halal tourism. This was confirmed from the results of interviews from the Manager's side. Homestay tourism villages on Lombok Island are not feasible to apply the principles of halal tourism, especially because Homestay Management has not been systematic, the Organizational Goals have not been set towards sharia Homestay, and the manager does not understand what sharia management is. From research, it is known that the weaknesses of homestays on Lombok Island are Culinary, Employees, Marketing, Rooms.